Pengaruh Beban Kerja dan Disiplin Kerja terhadap Kinerja Guru (Literature Review) - Ana Sichatul Fitria; Limgiani Limgiani (Journal of Student Research, 2024)
Teachers are tasked to realizing educational goals. Therefore, optimal teacher performance will always be needed in every school, so that the school's vision, mission and educational goals can be achieved. Teacher performance is influenced by many factors. Among them are workload and work discipline. The aim of this research is to determine the effect of workload and work discipline on teacher performance. This research uses a literature review, several articles identified using descriptive and exploratory analysis by comparing the results of each study. The research results show that 1). workload and work discipline have a positive and significant effect on teacher performance 2). Workload has a negative and significant effect on teacher performance if supported by other variables 3). Work discipline has a negative and significant effect on performance due to the need for communication between leaders and teachers.